How ICT Investment and Energy Use Influence the Productivity of Korean Industries - Nabaz T. Khayyat; Jongsu Lee; Almas Heshmati (Institute for the Study of Labor (IZA), 2014)
This empirical study examines changes in industrial productivity in Korea between 1980 and 2009, focusing on how investment in information and communication technology (ICT) and energy use, influence productivity levels. A dynamic factor demand model is applied in order to link inter-temporal production decisions by explicitly recognizing that the level of certain factors of production cannot be changed without incurring so-called adjustment costs, defined in terms of forgone output from current production. In particular, we investigate how the ICT–energy relationship affects total factor productivity growth in 30 industrial sectors. Describing industry-specific productivity levels is important for policymakers when the allocation of public investment and support is limited. The results presented herein show that ICT/non-ICT capital investment are substitutes for labor and energy use. We also find a high output growth rate in the sampled sectors, and increasing returns to scale, whose effects on the TFP component are higher than those of technological progress.
Keywords: C32; C33; Q41; 330; dynamic factor demand; panel data; ICT investment; energy use; productivity